Ethnomathematics in the rhythmic patterns of Bebano musical instruments of the Malay community of Riau Islands - Peratama, Affry Darmawan; Febrian, Febrian; Elvi, Marianti (Jurnal Gantang, 2024)
Bebano instrument is one of the traditional Malay musical instruments, a type of percussion or hit instrument. Most of the rhythm patterns in Malay music can be played with Bebano, namely langgam, zapin, inang, joget, and jogi rhythm patterns. This study aimed to determine the form of ethnomathematics in the rhythm patterns of Bebano musical instruments as mathematics learning materials. This study is qualitative research with an ethnographic approach. The research subjects were Penyengat Island art activists at Staman Malay Music. Data was collected by observation, interview, and documentation, with the main instrument being the researcher himself. Data analysis techniques included domain analysis, taxonomy, componential, and cultural themes. The study's results found the concept of mathematics contained in the rhythm patterns of Bebano musical instruments. In playing activities, mathematical material is found, namely variablizing and combination. While in the calculation activity, mathematical material is found, namely the form of fractional numbers.